Air Fryer Otomatis Berbasis Kendali Digital - Muji Burrochman; Indah Kurniawati; Reynanda Bagus Widyo Astomo (SinarFe7, 2022)
Air fryer is an electronic device used to cook food using air media. Frying without oil (air fryer system) has a procedure by utilizing the circulation of hot air from the heater and a mechanical fan which can reach approximately 200 degrees Celsius. This research aims is to determine the design model and the effectiveness of the design performance of an air fryer system using a microcontroller-based digital control. The results show the performance of the frying tool through the heating element and the max6675 sensor displayed on the LCD which is controlled by ESP 32. The frying of three foodstuffs, namely, sausage, nuggets, and potatoes is carried out by a heating element and the temperature is regulated via a thermostat using 100 degrees. It can be seen that the cooked results for sausages take 15 minutes, for nuggets it takes 18 minutes, and for potatoes it takes 22 minutes.